SENSITIVITY ANALYSIS OF TRANSPORTATION PRODUCTION COSTS IN INDONESIA - Ade Sjafruddin; Henry Armijaya; Agung Rahardjo; Ari Sarif Munandar (Jurnal Transportasi, 2008)
Abstract The transportation production cost (TPC) considerably has strong influence to the national economic condition. This paper focused on the analysis of the transportation production cost sensitivity in relation to the variation of the external affecting factor, which are fuel price, rupiah exchange rate and Bank of Indonesia interest rate. Based on the R2 values, the TPC components in general have significant correlation, with the fuel prices. However, they do not have high correlation to the fluctuation of interest rate and rupiah exchange rate. The sensitivity analysis shows that a 10% rise on fuel price would cause 6%, 2%, 7%, 2.4%, and 4.9% rise on the TPC of intercity bus, ferry ship, interisland ship, train, and airline, respectively.Keywords: sensitivity analysis, transportation production cost, external affecting factor.